Natural Ways of Learning Applied in Teaching Grammar to Young Learners in the Third Grade of SD Supriyadi Semarang in the Academic Year 2011-2012 - Ambarini, Ririn (ENCOUNTER, 2012)
Grammar is supposed to be taught to young learners in a kind of nature ways that students will not be aware that they are learning grammar. The approach that can be applied in teaching grammar to young learners is using game-like activities, role-playing/drama, and TPR. Those methods of teaching can be used in the process of teaching learning so that it can make the English lesson become fun and exciting for young learners. The aims of this research are to study and describe the development of childrenâs intelligence from the viewpoint of learning abilities and mention such methods that are related to natural ways of learning which follow the principles of the development. All the issues mentioned will be involved in the theoretical part. Using the natural ways of teaching Grammar techniques; puzzle in chain words, one word story game, literature in reading and writing story game, and TPR game was able to improve the studentsâ ability in mastering Grammar at the point of constructing positive, negative, and interrogative sentence that can be seen from the average of the pre-test score (72.19) and the post-test score (80.12). The result of the pre-test score was lower (72.19) than the post-test score (80.12). This research is quite urgent as the technique of teaching grammar that has already been applied in English class is still using the conventional technique. At present, most of the English teachers prefer giving the presentation of grammar theory to giving grammar activities that will enable students to learn without they are aware that they are studying grammar. In order to change the presentation of the materials that stil uses the conventional techniques in teaching grammar, it is important for English teachers to make the use of natural ways of learning techniques applied in teaching grammar to young learners.